Marginalizadas e transgressoras: um estudo da genealogia de Jesus segundo Mateus a partir das personagens feminina. - Xavier, Liniker Henrique (2018)
The Gospel of Matthew presents the genealogy of Jesus full of particularities. The main one is the insertion of five women in the text. This inclusion has precedents in the biblical text. Women appear in genealogies in Gn 11,29 and 1Ch 2: 18-21, for example. However, their participation prominently in a lineage is something quite unusual. In Matthew, what makes the episode even more exceptional is the fact that all four women who predate Mary have serious moral issues in their biographies, all of which are linked to the sexual issue. The life of Tamar, Rahab, Ruth, and Bathsheba, flow into the story of Mary, the bride of Joseph who, without sexual intercourse, becomes pregnant. They are marginalized and transgressive women by participating in the lineage of the messiah in a text written especially for the Jew who believes in Jesus as the Son of God. In this way, the questions revolve around why Matthew inserted women into a genealogy that would be read by a particularly androcentric society. More than that, why the women mentioned are the transgressors and not matriarchs like Sara and Rebecca, for example? To arrive at possible solutions to these questions, let us work on the question of genealogy as a literary genre within the Bible and in what form this genre was used. After we understand the literary characteristics of the text, let us understand the particularities of Mt 1,1-17 before we study the situation of women in the context of ancient Israel. Matters involving the life of the women of Matthew genealogy will be analyzed, among them marriage, polygamy, adultery, and divorce. In addition to ancient Israel, we will also approach the woman in the gospel of Matthew, before we learn the life stories of Tamar, who became pregnant with her father-in-law Judah; Rahab the Canaanite prostitute; Ruth, who seduced Boaz; Bathsheba, the wife of Uriah, who was a lover of king David before she became a wife; and, finally, Mary, the virgin who becomes pregnant by the work of the Holy Spirit. All of these women are involved in issues that, in the light of the ethics and morals of the Hebrew people, discredit them to participate in the genealogical tree of Jesus, but nothing in their past was enough to drive them away from the messiah.